Chikungunya virus entry is strongly inhibited by phospholipase A2 isolated from the venom of Crotalus durissus terrificus - Santos, Igor Andrade; Shimizu, Jacqueline Farinha [UNESP]; de Oliveira, Débora Moraes; Martins, Daniel Oliveira Silva [UNESP]; Cardoso-Sousa, Léia; Cintra, Adélia Cristina Oliveira; Aquino, Victor Hugo; Sampaio, Suely Vilela; Nicolau-Junior, Nilson; Sabino-Silva, Robinson; Merits, Andres; Harris, Mark; et al. (My University, 2021)
Chikungunya virus (CHIKV) is the etiologic agent of Chikungunya fever, a globally spreading mosquito-borne disease. There is no approved antiviral or vaccine against CHIKV, highlighting an urgent need for novel therapies. In this context, snake venom proteins have demonstrated antiviral activity against several viruses, including arboviruses which are relevant to public health. In particular, the phospholipase A2CB (PLA2CB), a protein isolated from the venom of Crotalus durissus terrificus was previously shown to possess anti-inflammatory, antiparasitic, antibacterial and antiviral activities. In this study, we investigated the multiple effects of PLA2CB on the CHIKV replicative cycle in BHK-21 cells using CHIKV-nanoluc, a marker virus carrying nanoluciferase reporter. The results demonstrated that PLA2CB possess a strong anti-CHIKV activity with a selectivity index of 128. We identified that PLA2CB treatment protected cells against CHIKV infection, strongly impairing virus entry by reducing adsorption and post-attachment stages. Moreover, PLA2CB presented a modest yet significant activity towards post-entry stages of CHIKV replicative cycle. Molecular docking calculations indicated that PLA2CB may interact with CHIKV glycoproteins, mainly with E1 through hydrophobic interactions. In addition, infrared spectroscopy measurements indicated interactions of PLA2CB and CHIKV glycoproteins, corroborating with data from in silico analyses. Collectively, this data demonstrated the multiple antiviral effects of PLA2CB on the CHIKV replicative cycle, and suggest that PLA2CB interacts with CHIKV glycoproteins and that this interaction blocks binding of CHIKV virions to the host cells.